ASHY DERMATOSIS ASSOCIATED WITH ORAL ANTIDEPRESSANTS - Filho, Fred Bernardes (2013)
Ashy dermatosis or erythema dyschromicum perstans (EDP) is a clinical syndrome with a controversial classification. The condition is rare in Brazil. It was initially reported in El Salvador but has also been found in several South American countries and in other regions of the world. Its etiology is unknown; however, some authors believe that it represents a diffuse presentation of fixed drug eruption, while others consider it to be a variant of lichen planus pigmentosus in view of the similar histopathological findings. Clinically, the condition presents with lesions in the form of numerous gray macules of varying sizes. There is no effective treatment to date; however, benefits have been repor- ted with the use of clofazimine. In this report, the authors describe a case of ashy dermatosis associated with the use of serotonin-specific reuptake inhibitors. KEYWORDS – Skin diseases; Erythema; Hyperpigmentation; Drug eruptions; Lichen planus.